New stratigraphic units of beds with the conchostracan fauna in the Upper Permian and Lower Triassic deposits of Eastern Europe and Siberia - V.V. Zharinova (Учёные записки Казанского университета: Серия Естественные науки)
The biostratigraphic analysis of conchostracans from the territory of Eastern Europe was based on the study of sections of the Middle–Upper Permian and Lower Triassic deposits of the Upper Volga, Middle Volga–Kama, Dvina–Mezen, and Pechora districts, all, except for the last one, belonging to the Euramerian paleozoogeographic region. The biostratigraphy of conchostracans from the territory of Siberia was performed by investigating the territories of the Angara paleozoogeographic region: Upper Permian and Lower Triassic sections of the Kuznetsk Basin, the Siberian Platform, and the Southern Verkhoyansk Region. The conchostracan samples were collected during the field expeditions. To reconstruct their distribution in the sections of the Euramerian and Angara paleozoogeographic regions, the literature data were also used. The quantity and quality of the studied material determined the degree of detail achieved. Beds containing conchostracans were identified in the Severodvinian, Vyatkian, Induan, and Olenekian deposits of different territories of the Euramerian and Angara paleozoogeographic regions. Beds with Estheria elongata were revealed in the Putyatino Horizon of the Severodvinian Stage of the Upper Volga, Middle Volga–Kama, and Dvina–Mezen basins. Beds with Megasitum volgaense were found in the Zhukov Horizon of the Vyatkian Stage of the Upper Volga and Middle Volga–Kama basins, as well as in the Gagarjeostrov and Ivakin Horizons of Upper Permian deposits of the Siberian Platform. Beds with Euestheria gutta were discovered in the Induan and Olenekian deposits of different territories of Eastern Europe and Siberia.